A study of the information acquisition behaviour of small and medium sized manufacturing enterprises in New Zealand : a thesis presented in partial fulfilment of the requirements for the degree of Masters of Philosophy in Product Development at Massey University - Gomes, Christina Melody (Massey University, 1998)
Access to scientific and technological information enables companies to be more aware of new developments in technology and the resources available for obtaining and using the technology correctly. Harnessing a clear understanding of the technological and market environment is essential for most small businesses to improve their competitive position and face up to increasing national and international competition. This study investigates the information acquisition behaviour of small and medium sized manufacturing enterprises (SMEs) in New Zealand, where SMEs not only dominate manufacturing employment but constitute 99.5% of all New Zealand companies. Using a questionnaire methodology, this thesis reports an empirical study of the information acquisition characteristics and performance of 132 SMEs. Recent years have witnessed increasing international interest by academics, managers and policy writers, in the role of information within the business environment. However, information acquisition is seldom publicly discussed in relation to SMEs and is significantly absent from scholarship. To date very few studies have investigated how SMEs acquire information, how they disseminate this resource through their organisation and subsequently, if any barriers inhibit effective information infusion. The results of this thesis demonstrate that SME owner/managers rely heavily on their own personal experience and judgment when making decisions. Information acquisition within SMEs is primarily a reactive procedure, where information is acquired to solve a specific problem. Criteria such as the inhibiting feature of individualism, a lack of managerial competence, resource deficiencies and the turbulent economic environment facing SMEs, suggest there is merit in seeking government support to develop an information assistance programme for the small business sector.
Keywords: Small business; Technological innovations; Management; New Zealand; Information services